Effect of combination hepatoprotective therapy with sulfur-containing drugs on oxidative homeostasis in the blood of patients with alcoholic hepatitis: A randomized prospective study - I. M. Bykov; G. A. Ermakova; K. A. Popov; M. A. Popova; A. G. Zavgorodnyaya; E. S. Ustinova (Кубанский научный медицинский вестник, 2024)
Background. The study aims to evaluate the efficacy of combination hepatoprotective therapy for alcoholic liver damage. Given the difference in the mechanism of action and the experimentally demonstrated cytoprotective efficacy of ademetionine and lipoic acid, these drugs could be expected to potentiate each other’s effects. Objective. To determine the effect of the combined use of ademetionine and lipoic acid on the cytolytic syndrome and oxidative metabolism in the blood of patients with alcoholic hepatitis. Methods. A randomized prospective study was conducted examining 30 patients diagnosed with alcoholic liver disease and 15 healthy individuals. The patients were treated at the Drug Abuse Clinic of the Krasnodar Krai Ministry of Health, whereas healthy volunteers were monitored at the Clinic of the Kuban State Medical University (2022–2024). The study included male patients aged 20 to 40 years with a diagnosis of alcoholic liver disease in the form of alcoholic hepatitis. Patients with other decompensated somatic and psychiatric disorders were excluded from the study. Via simple randomization with the use of random number tables, the patients were distributed into three groups. Group 2 patients received ademetionine (400 mg intravenously per day, Hepcifol). Group 3 patients were administered lipoic acid (600 mg intravenously per day, Octolipen). Group 4 patients received combination therapy with the administration of ademetionine and lipoic acid in the specified dosages and forms. The inpatient treatment lasted 15–18 days; on admission and prior to discharge, the patients had their blood samples taken. Blood serum was assayed for the activity of hepatocyte cytolysis markers and the concentrations of total protein, albumin, and bilirubin, as well as total antioxidant activity and thiol group content. The concentrations of glutathione and thiobarbituric acid reactive substances were determined in erythrocytes. The data were statistically processed using Statistica 10 (StatSoft, Inc., 2011). The differences between the parameters of the groups were considered statistically significant at p < 0.05. Results. Following a three-week course of treatment, the combination therapy with two sulfur-containing hepatoprotectors helped to achieve 1.7–2.1 times lower activity of alanine aminotransferase and gamma-glutamyltransferase in blood plasma as compared to the corresponding markers in the groups of patients receiving only one of the drugs. The therapy with sulfur-containing drugs was accompanied by tendencies toward normalization of free radical homeostasis. The maximum effects were achieved when lipoic acid was used alone or together with ademetionine. In this case, a 52–64% increase in the antioxidant activity of blood plasma was observed, with the concentration of thiobarbituric acid reactive substances decreasing by 28–36%. Conclusion. The combination therapy with the use of sulfur-containing hepatoprotectors helped to achieve the lowest possible enzyme activity (cytolytic syndrome markers) in patients with alcoholic hepatitis